التّدابير الشّرعيّة والطّبّيّة للوقاية من كورونا المستجدّ (كوفيد-19): دراسة تحليليّة - Muneer Ali Abdul Rab; Baidar Mohammed Mohammed Hasan; Setiyawan Bin Gunardi; Mesbahul Hoque (USIM Press (Penerbit USIM), 2024)
Vol. 10 No. 1 (2022): MJSL - Volume 10, No. 1, 2022